Improving pelvic floor muscle strength in women with postpartum stress urinary incontinence using electromagnetic stimulation therapy: A randomized controlled trial - Roziana, Roziana; Chan, Muhammad SN.; Santoso, Budi I.; Sjusad, Suskhan; Priyatini, Tyas; Hakim, Surahman; Moegni, Fernandi; Mutia, Alfa P.; Kurniawan, Andrew P.; Armita, Nurdarlila (Narra J, 2025)
Electromagnetic stimulation (EMS) has emerged as a potential alternative for managing urinary incontinence in women. However, research directly comparing EMS to Kegel exercises in cases of postpartum stress urinary incontinence (SUI) is limited. The aim of this study was to assess the effectiveness of EMS (improvement of the symptoms, incontinence severity and pelvic floor muscle strength) and patient compliance with the therapy in postpartum women with SUI. A single-blind randomized clinical trial was conducted involving postpartum women diagnosed with SUI at least three months after delivery. The EMS group received the therapy three times a week for five weeks, while the Kegel group was instructed to perform daily exercises for eight weeks. Improvement of the symptoms and incontinence severity were evaluated using the Urogenital Distress Inventory-6 (UDI-6) and a 1-hour pad test, respectively, while pelvic floor muscle strength was measured with a perineometer. Both groups showed significant improvements in UDI-6 scores, 1-hour pad test results and pelvic floor muscle strength compared to before treatment. However, the EMS group had significantly greater muscle strength than the Kegel group (16.5 vs 8.0 cmH2O, p=0.006). The UDI-6 scores, 1-hour pad test results and patients’ compliance were not significantly different between EMS and Kegel groups. EMS demonstrated a greater ability to enhance pelvic floor muscle strength than Kegel exercises. These findings suggest that EMS may be a more effective option for enhancing pelvic floor muscle strength in postpartum women.